2013
DOI: 10.1525/cond.2012.120011
|View full text |Cite
|
Sign up to set email alerts
|

Landbird Assemblages in Different Agricultural Landscapes: A Case Study in the Pampas of Central Argentina

Abstract: Abstract. A combination of elements (e.g., crops and pasture lands, strips of roadside vegetation, woodlots, temporary wetlands) increases the heterogeneity of rural landscapes. Agricultural landscapes range from homogeneous, dominated by a single element (i.e., pure cropland or pure pastoral farming) to heterogeneous, dominated by two or more elements (i.e., mixed farming). In this study we characterized landbird assemblages in various agricultural landscapes (cropland, pastoral, and mixed landscapes) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 48 publications
(62 reference statements)
3
41
0
9
Order By: Relevance
“…Thus, the matrix of scarce cropland and abundant natural or semi-natural grasslands seem to favor D. hybridus (Abba et al, 2007;Abba and Vizcaíno, 2011). Similar responses of vertebrates to dominant landscape matrix in the study area have also been reported for small mammals and birds (Codesido et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, the matrix of scarce cropland and abundant natural or semi-natural grasslands seem to favor D. hybridus (Abba et al, 2007;Abba and Vizcaíno, 2011). Similar responses of vertebrates to dominant landscape matrix in the study area have also been reported for small mammals and birds (Codesido et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…The effects of this recent agriculturization on biodiversity has already been detected in both birds (Codesido et al, 2008(Codesido et al, , 2013Filloy and Bellocq, 2007;Weyland et al, 2014) and small mammal assemblages at landscape and regional scales González-Fischer et al, 2011. Additionally, effect of land use on armadillos has been observed at a local scale in a livestock area of the Flooding Pampas, where D. hybridus was associated with natural grasslands and avoided cultivated pastures (Abba et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…The species recorded in DHWR showed a high specificity in the use of habitat which is consistent with a close relationship between bird species and structural and floristic characteristics of the vegetation (Graham and Blake 2001;Naugle et al 2001;Skowno and Bond 2003;Wakeley et al 2007;Di Giacomo and Lopez De Casenave 2010). This suggests that increasing complexity in habitat structure (horizontal, vertical and qualitative variation of elements present) generates greater resources for birds, allowing the persistence of a greater number of species and guilds than in less complex habitats (MacArthur and MacArthur 1961;Tews et al 2004;Codesido et al 2013).…”
Section: Discussionsupporting
confidence: 64%
“…Also, moderate grazing rates may provide grass coverage and height similar to those of natural grasslands, as found in the rangelands of North America (Peterjohn 2003). Furthermore, pastures may offer horizontal and vertical structural diversity for birds nesting on the ground, such as the Burrowing Owl (Athene cunicularia; Pairo et al 2017), or on grasses, such as the Great Pampa-Finch (Embernagra platensis), the Brown-and-yellow Marshbird (Pseudoleistes virescens), the Hudson's Canastero (Asthenes hudsoni), and the Greater Rhea (Rhea americana; Codesido et al 2013). Also, grazing management could be used in the restoration of seminatural grasslands (WallisDeVries et al 1998).…”
Section: Discussionmentioning
confidence: 99%